1987
DOI: 10.1023/a:1016404111054
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Earlier studies of the hydrolysis and aminolysis of penicillin, in the presence of zinc ion and tromethamine (Tris), revealed a very rapid catalysis mediated by a ternary complex in which the metal ion brought the reactants into close proximity in a suitable configuration for reaction. In the present work similar studies with a group of cephalosporins show not only much slower rates of reaction but a different mechanism in which the zinc ion-tromethamine complex functions as a nucleophile in a bimolecular reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The decrease of DS release from 27/3 liquid suppository suggests that P407 concentration was the main factor affecting drug release. These results are in agreement with the release data those reported by Tomida et al 29 .…”
Section: Gelationsupporting
confidence: 94%
“…The decrease of DS release from 27/3 liquid suppository suggests that P407 concentration was the main factor affecting drug release. These results are in agreement with the release data those reported by Tomida et al 29 .…”
Section: Gelationsupporting
confidence: 94%
“…15,16 Tomida et al proposed that, for the release of a drug into aqueous solution to be pH-dependent, it must be weakly acidic or basic and have low aqueous solubility. 17 Ibuprofen satisfies these criteria. Altering the solubility of a drug in a Pluronic solution, by varying the pH of the solvent, has also been found to influence sol-gel transition boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Unfunctionalized Pluronic copolymers are not expected to exhibit strong pH sensitivity, since they do not contain ionizable groups . However, several research groups have reported Pluronic gel systems which show pH-dependent release of acidic or basic drugs, including the nonsteroidal drugs ketoprofen, naproxen, and diclofenac. , Tomida et al proposed that, for the release of a drug into aqueous solution to be pH-dependent, it must be weakly acidic or basic and have low aqueous solubility . Ibuprofen satisfies these criteria.…”
Section: Introductionmentioning
confidence: 99%